Implementation of Chemical Instrumentation Competency-Based Learning for Chemical Lecturers At Medical Laboratory Technology Program - Endang Tri Wahyuni Maharani; Andari Puji Astuti; Yusrin Yusrin (THABIEA : JOURNAL OF NATURAL SCIENCE TEACHING, 2022)
The research background is that the chemical instrumentation course examines all instrumentation used in health laboratory examinations according to the demands of the competence of a Health Analyst. In addition to the demands of professionalism (hard skills), the success of learning is also determined by the soft skills of the lecturers. In terms of challenges in the learning process, training is a solution to overcome these problems. The aim of this research is to analyze the factual, hypothetical and final models of chemical instrumentation training management for Chemistry Medical Laboratory Technology lecturers. The research design used Research and Development (R&D) within 3 (three) stages, namely: preliminary, development, and testing which was conducted towards the Chemistry lecturers of Medical Laboratory Technology program in Semarang City. Data collection techniques used: interviews, instruments, and documents. The feasibility of the model was tested through expert and practitioner validation tests and limited experiments through Focus Group Discussion (FGD). The research data were analyzed descriptively, quantitatively and qualitatively. The research results in several conclusions: 1) the training management model for Chemistry Medical Laboratory Technology lecturers that has been implemented so far has not been able to accommodate the aspirations of lecturers teaching chemical instrumentation material; 2) development of the design of a chemical instrumentation training management model for Chemistry Analyst lecturers includes the implementation of training, training organization, training implementation, and training evaluation which is carried out comprehensively starting from teaching materials, programs, procedures, instructors, facilities and infrastructure; and 3) the design development of a chemical instrumentation training management model for Chemistry Medical Laboratory Technology lecturers is feasible to be applied in training, because it has practicality, usefulness, and effectiveness through validation of experts in their fields and individual, group and limited tests have been carried out with good criteria. In general, the chemical instrumentation training management model is better than the existing model, easier to understand, easier to implement, and more complete in its management elements, both planning, organizing, implementing, evaluating, monitoring, and following up after training.